THE IMPORTANCE OF THE MEDIA IN THE PROCESSES OF CIVIL SOCIETY DEVELOPMENT IN UZBEKISTAN - Ulugbek Hayitov (Journal Park Publishing, 2023)
The role of mass media in the process of formation and development of a legal democratic state and civil society, as well as ensuring public and parliamentary control over the activities of state power and management bodies, establishing strong relations between the government and the public, their place in the system of civil society institutions and The features, functions and significance of the constitutional rights and freedoms aimed at strengthening the role of citizens and ensuring the freedom of speech are briefly described.
Keywords: legal democratic state, civil society, mass media, democracy. public control, role of mass media, functions of mass media, social opinion, mass media, socio-political life.